A Colour Perception Detection Model Based on The Spectral Characterictics - Irwan anto Mina (President University, 2019)
Information needs for one's color perception are needed in the fields of medicine, engineering, astronomy, biomedicine and so on. The demand for accurate assessment of color perception must be met by the perception detection tool used. Ishihara's test, as a perception detection tool that is still used today has insufficient accuracy. This research aims to create a system that can detect a shift in one's color perception, relative to the average color perception of a number of respondents. Through plotting the respondents' perception points, in the CIE coordinate system (Commission International de I'Eclairage) XYZ can be calculated the average euclidean distance, ED, relative to the reference point and the distribution of x and y groups of perception points around the point of reference. Both size, euclidean distance and distribution are used as indicators of average color perception so that an assessment of one's color perception is given based on the results of comparison between color perception points and color perception indicators. The tool used to do the test is Delphi version 7.0 software. the research material used is the RGB (Red, Green, Blue) color image format. The results of a person's color perception study are divided into three levels, namely: (1)